THE EFFECT OF PROBLEM-BASED LEARNING ORIENTED WITH TRADITIONAL GAMES ON STUDENTS LEARNING OUTCOMES VIEWED FROM HAND-EYE COORDINATION - Aryananda, I Putu Gede; Parwata, I Gusti Lanang; Wijaya, Made Agus (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
The current study aimed at investigating the effect of problem-based learning oriented with traditional games on students learning outcomes viewed from hand-eye coordination. Quasi-experimental was used as a research design since the current study was conducted in the form of quantitative research. The research setting was SDN 6 Batubulan, Gianyar, Bali. There were 40 of fifth-grade students that were involved as a research sample. They were selected by using simple random sampling. They were divided into control and experimental group by using order vairing technique. The data were obtained by conducted pretest and posttest. The performance test and written test were conducted during the pretest and posttest. The test rubrics were used as research instruments. The data were analysed by using inferential analysis (Two-Way ANOVA and Independent Sample T-test) with the assistance of SPSS 25. The results indicated that there was an impact on students’ learning outcomes due to their hand-eye coordination ability and the implementation problem-based learning oriented with hand-eye coordination.